Respostas

2013-12-04T03:25:02-02:00
Por substituição:
y + x = 8
y = 8-x

substituindo o y na outra equação...

x² + y² = 34
x² + (8-x)² = 34
x² + 64 - 16x + x² = 34
2x² - 16x + 30 = 0 (equação do 2º grau)

As raízes são:
x' = 3
x'' = 5

Logo,
Ou o x = 3 ou o x = 5.

Beleza..

1 5 1
2013-12-04T08:23:46-02:00
X²+y² = 34
x+y = 8 --> y = 8-x
x²+(8-x)² = 34
x²+64-16x+x² = 34
2x²-16x+64-34 = 0
2x²-16x+30 = 0 (:2)
x²-8x+15 = 0
Δ = b²-4ac
Δ = (-8)²-4.1.15
Δ = 64 - 60
Δ = 4
x = (-b+/-√Δ)/2a
x = (-(-8)+/-√4)/2
x = (8+/-2)/2
x' = (8+2)/2 --> x' = 10/2 --> x' = 5
x" = (8-2)/2 --> x" = 6/2 --> x" = 3
y' = 8-x' --> y' = 8-5 --> y' = 3
y" = 8-x" --> y' = 8-3 --> y" = 5
S:{(5,3),(3,5)} --> Conclusão: x = 3 ou x = 5